Sintered body of particles of nasicon-based solid electrolyte
By mixing pearlicon-type solid electrolytes with aluminum oxide and sintering at specific temperatures, a dense, water-resistant sintered body is achieved, addressing the precision and water resistance issues in hybrid secondary batteries.
Patent Information
- Application Number
- JP2023119414
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-21
- Publication Date
- 2025-01-31
AI Technical Summary
Existing methods for sintering pearlicon-type solid electrolytes fail to achieve the necessary precision and water resistance required for use in water-based-non-water-based hybrid secondary batteries, and existing sintering assistants lack the necessary water resistance for this application.
A simple method involving mixing pearlicon-type solid electrolytes with aluminum-containing oxide powders and sintering at specific temperatures to create a dense, water-resistant sintered body.
The method produces a sintered body with excellent precision and water resistance, suitable for use as a separator in water-based-non-water-based hybrid secondary batteries, demonstrating improved density and reduced water permeability.
Smart Images

Figure 2025016262000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a sintered body of Nasicon-type solid electrolyte particles, more specifically, to a dense sintered body of Nasicon-type solid electrolyte particles useful as a separator for aqueous-nonaqueous hybrid secondary batteries. [Background technology]
[0002] In recent years, the development of innovative next-generation batteries aimed at highly efficient use of renewable energy has been attracting attention. As a specific example, an electrochemical secondary battery device (seawater secondary battery) has been proposed that uses seawater as the electrolyte on the positive electrode side. Such seawater secondary batteries have the structure of an aqueous-nonaqueous hybrid secondary battery, in which an aqueous electrolyte is used on the positive electrode side and a nonaqueous electrolyte is used on the negative electrode side, and the electrolytes are separated by a sodium ion conductive solid electrolyte separator (Non-Patent Document 1, Non-Patent Document 2).
[0003] As a sodium ion conductive solid electrolyte separator, a sintered body of a Nasicon type solid electrolyte is used. The most common method for obtaining a sintered body of a Nasicon type solid electrolyte is to compact a powder of the solid electrolyte and then sinter it to make it dense. For example, Na 3 Zr 2 (SiO 4 ) 2 PO 4 When using NZSP (hereinafter also referred to as "NZSP"), the sintering process is usually carried out at a temperature just below the melting point of NZSP, i.e., about 1250°C to 1270°C, in order to improve the density of the sintered body. On the other hand, sintering at high temperatures exceeding 1250°C can generally cause composition changes due to the volatilization of light elements such as sodium and phosphorus, and phase transitions to structures with low ionic conductivity. Therefore, it is considered important to devise ways to obtain higher density by sintering at lower temperatures.
[0004] In order to improve the performance of sintered bodies of Nasicon-type solid electrolytes at low temperatures, various sintering methods have been proposed. One example of such a sintering method is a method using a sintering aid. Specifically, sodium niobium phosphate glass Na 2 O-Nb 2 O 5 -P 2 O 5 It has been reported that by adding sodium borate (hereinafter also referred to as "NNP") powder as a sintering aid to NZSP powder, a sintered body with good density can be obtained in the sintering temperature range of about 900°C (Non-Patent Document 3). 3 BO 3 It has been reported that the use of NBO makes it possible to improve density in the sintering temperature range of about 900° C. (Non-Patent Document 4).
[0005] Another example of the sintering method is a method of doping aluminum element into NZSP. 2 O 3 , Na 2 CO 3 , ZrO 2 , SiO 2 , Na 3 PO 4 By mixing the raw materials such as Al in a specified amount and carrying out a solid-state sintering reaction, 3+ A method has been reported in which Al-doped NZSP particles are synthesized, and then the Al-doped NZSP particles are compacted and sintered (Patent Document 5). [Prior art documents] [Non-patent literature]
[0006] [Non-Patent Document 1] Energy Storage Materials, Volume 16, January 2019, Pages 56-64 [Non-Patent Document 2] Advanced Science, Volume 7, Issue 5, 2020, 1902866 [Non-Patent Document 3] Solid State Ionics, Volume 269, January 2015, Pages 19-23 [Non-Patent Document 4] Journal of the American Ceramic Society, Volume101, Issue3, 2018, Pages 1255-1265 [Non-Patent Document 5] Journal of Materials Science volume 28, pages 1573-1577 (1993) Summary of the Invention [Problem to be solved by the invention]
[0007] In order to realize stable operation and high electromotive force of the battery, the sintered body of Nasicon-type solid electrolyte used as the solid electrolyte separator of aqueous-nonaqueous hybrid secondary battery needs to have the property of preventing water penetration into the negative electrode at the molecular level. From this point of view, the sintered body of Nasicon-type solid electrolyte used as the solid electrolyte separator of aqueous-nonaqueous hybrid secondary battery needs to have high density (water impermeability) and water resistance (chemical and physical stability against water).
[0008] However, simply sintering particles of a Nasicon-type solid electrolyte at a temperature just below its melting point does not provide a sintered body with sufficient density.
[0009] Although the method of using NNP or NBO as a sintering aid can increase the density of the sintered body, the sintering aid itself does not have water resistance, and therefore the sintered body obtained by using such a sintering aid can only be applied to non-aqueous batteries, and essentially cannot be applied to aqueous-non-aqueous hybrid secondary batteries.
[0010] In addition, sintered bodies of Al-doped NZSP particles are expected to be water-resistant and dense. However, the solid-phase synthesis method for obtaining Al-doped NZSP particles generally requires complex and advanced control, such as control of the phase purity of the product, suppression of impurity phases, control of the particle size of the product, and removal of unreacted components, and is by no means simple.
[0011] SUMMARY OF THE PRESENT EMBODIMENT An object of the present invention is to provide a sintered body of Nasicon type solid electrolyte particles which has excellent density and water resistance and can be produced without requiring complex and advanced control. [Means for solving the problem]
[0012] As a result of intensive research, the inventor of the present invention has unexpectedly found that a sintered body of Nasicon-type solid electrolyte particles with excellent water resistance and excellent density can be obtained by a very simple method of mixing Nasicon-type solid electrolyte particles with aluminum-containing oxide powder and compacting and sintering them. The present invention was completed by further research based on this finding.
[0013] That is, the present invention provides the following aspects. Item 1. A sintered body of particles of a Nasicon type solid electrolyte, comprising the particles, and A sintered body comprising a grain boundary phase made of a melt-solidified product of the solid electrolyte and an aluminum-containing oxide, which bonds the particles together. Item 2. The sintered body according to Item 1, wherein the Nasicon-type solid electrolyte is a sodium-containing oxide. Item 3. The sodium-containing oxide is Na 3 Zr 2 (SiO 4 ) 2 PO 4 Item 3. The sintered body according to Item 2, Item 4. A method for producing a sintered body of particles of a Nasicon type solid electrolyte, comprising: The method includes a step of compacting and sintering a mixed powder containing particles of the solid electrolyte and particles of an aluminum-containing oxide. Item 5. The method according to Item 4, wherein the powder sintering temperature is 1100 to 1250°C. Item 6. The method according to item 4 or 5, wherein in the mixed powder, the content of the aluminum-containing oxide particles is 1 to 25 mol % per 100 mol % in total of the solid electrolyte particles and the aluminum-containing oxide particles. Item 7. A solid electrolyte separator for an aqueous-non-aqueous hybrid secondary battery, comprising the sintered body according to any one of items 1 to 3. Item 8. An aqueous-nonaqueous hybrid secondary battery comprising: a positive electrode-side aqueous electrolyte; a negative electrode-side nonaqueous electrolyte; and the solid electrolyte separator according to item 7 interposed between the electrolytes. Effect of the Invention
[0014] According to the present invention, there is provided a NASICON-type solid electrolyte particle sintered body having excellent density and water resistance, which can be produced without requiring complex and advanced control. [Brief description of the drawings]
[0015] [Figure 1] 1 shows a comparison of scanning electron microscope images (secondary electron images) of NZSP sintered bodies produced using 0 mol % (Comparative Example 1) or 5 mol % (Example 1) of Al2O3. The fracture surfaces of the sintered bodies were observed at an accelerating voltage of 4 kV. [Diagram 2] This is a comparison of scanning electron microscope images (secondary electron image and backscattered electron image) of the fracture surface of the sintered body of Example 1, which was produced by adding 5 mol% Al2O3. The fracture surface of the sintered body was observed at an accelerating voltage of 4 kV. The secondary electron image and backscattered electron image were obtained at the same location at the same time. [Diagram 3] Energy dispersive X-ray (EDS) spectra obtained from each point (Sp.1, Sp.2) in the backscattered electron image are shown. [Figure 4] 1 shows XRD profiles of the sintered body of Example 1 (5 mol% Al2O3), the sintered body of Comparative Example 1 (0 mol% Al2O3), and the untreated original material NZSP powder. [Diagram 5](a) Cross-sectional view of the electrochemical cell used in the water permeability evaluation test (b) Results of a cyclic voltammetry test of electrochemical cells fabricated using ceramic sample plates made from the sintered body of Example 1 (5 mol% Al2O3) and the sintered body of Comparative Example 1 (0 mol% Al2O3). [Figure 6] (a) Cross-sectional view of the aqueous-nonaqueous hybrid sodium battery structure. The negative electrode active material was Na3LiTi5O12 (NTO), and the nonaqueous electrolyte was 1M NaTFSA in EC / DEC=1.0. A glass filter with a thickness of t=0.2 mm was sandwiched between the negative electrode active material and the NZSP sintered ceramic sample plate of Example 1. (b) Results of a cyclic voltammetry test of the electrochemical cell shown in (a), measured using a Pt ribbon as the counter electrode and a silver / silver chloride electrode as the reference electrode. [Figure 7] Results of cyclic voltammetry tests on a prototype aqueous-nonaqueous hybrid sodium battery. Hydrogen peroxide was added to the electrolyte of the positive electrode as a sacrificial redox agent, creating a 3wt%H2O2-0.5M Na2SO4aq electrolyte. [Figure 8] 1 shows the appearances of the sintered bodies of Comparative Examples 1 and 2 and Examples 2 and 3. [Figure 9] 1 shows the results of a water leakage electrochemical test of ceramic sample plates made from the sintered bodies of Comparative Examples 1 and 2 and Examples 2 and 3. [Figure 10] 1 shows a comparison of the results of a cyclic voltammetry test evaluating water permeability due to differences in the amount of alumina added (Examples 2, 4, and 5 and Comparative Example 1). [Figure 11] FIG. 6(a) shows cycle characteristics in a cyclic voltammetry test in a cell having the same configuration as in FIG. 6(a) when the negative electrode electrolyte was gelled. [Figure 12] 1 shows the results of differential thermal analysis of the sintered bodies of Comparative Example 1 and Example 6. [Figure 13] The results of a cyclic voltammetry test evaluating the water permeability of ceramic sample plates made from the sintered bodies of Comparative Examples 1 and 3 and Examples 2, 4, 5, 7, and 8 are shown. [Figure 14] 1 shows a scanning electron microscope (SEM) secondary electron image of the sintered body of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] [1. Sintered particles of Nasicon-type solid electrolyte] The sintered body (Nasicon ceramics) of the particles of the Nasicon type solid electrolyte of the present invention is characterized by comprising the grain boundary phase consisting of the molten solidified material of the solid electrolyte and the aluminum-containing oxide, which bonds the particles together. In other words, the sintered body (Nasicon ceramics) of the particles of the Nasicon type solid electrolyte of the present invention is characterized by the grain boundary phase consisting of the particles and the gaps between the particles being filled with the molten solidified material produced by the reaction between the solid electrolyte and the aluminum-containing oxide, and being densified.
[0017] The NASICON (Na super ionic conductor) type solid electrolyte is not particularly limited as long as it has a NASICON type crystal structure. The NASICON type crystal structure is a structure in which MO6 octahedrons (M represents a transition metal) and AO4 tetrahedrons (A represents S, P, As, Mo, W, etc.) are arranged three-dimensionally with their vertices shared. This structure often has large voids and bottlenecks in the crystal structure, so it has excellent ionic conductivity for cations such as Li ions or Na ions.
[0018] Examples of the Nasicon-type solid electrolyte of the present invention include sodium-containing oxides and lithium-containing oxides, and preferably sodium-containing oxides.
[0019] The sodium-containing oxide having a Nasicon structure is specifically represented by the general formula Na s X 1 t X 2 u O v In this case, the compound represented by the formula: 1 represents at least one selected from Al, Y, Yb, Nd, Nb, Ti, Hf and Zr, and preferably represents at least one selected from Y, Nb, Ti and Zr. 2represents at least one selected from Si and P. s represents 1.4 to 5.2, t represents 1 to 2.9, u represents 2.8 to 4.1, and v represents 9 to 14.
[0020] A more specific example of the Nasicon-type solid electrolyte of the present invention is Na 3 Zr 2 S 2 PO 12 , Na 3.2 Zr 1.3 S 2.2 P 0.8 O 10.5 , Na 3 Zr 1.6 Ti 0.4 S 2 PO 12 , Na 3 Hf 2 S 2 PO 12 , Na 3.4 Zr 0.9 Hf 1.4 Al 0.6 S 1.2 P 1.8 O 12 , Na 3 Zr 1.7 Nb 0.24 S 2 PO 12 , Na 3.6 Ti 0.2 Y 0.8 S 2.8 O 9 , Na 3 Zr 1.88 Y 0.12 S 2 PO 12 , Na 3.12 Zr 1.88 Y 0.12 S 2 PO 12 , Na 3.6 Zr 0.13 Yb 1.67 S 0.11 P 2.9 O 12 , Na 5 YSi 4 O 12 and the like, and preferably Na 3 Zr 2 S 2 PO12 (That is, Na 3 Zr 2 (SiO 4 ) 2 PO 4 :NZSP) are examples.
[0021] The melt-solidified material of the Nasicon-type solid electrolyte and the aluminum-containing oxide fills the space between the particles of the Nasicon-type solid electrolyte (i.e., the grain boundary phase), thereby bonding the solid electrolyte particles together and improving the density of the sintered body. This melt-solidified material is formed by solidifying the melt generated by the reaction of the Nasicon-type solid electrolyte and the aluminum-containing oxide. The melt-solidified material may be crystalline, may be amorphous, or may be a mixture of both. The sintered body of the present invention achieves high density as a sintered body because the grain boundary phase of the particles of the Nasicon-type solid electrolyte is filled with the melt-solidified material.
[0022] [2. Manufacturing method of sintered particles of Nasicon-type solid electrolyte] The method for producing a sintered body of a Nasicon-type solid electrolyte of the present invention is a method for producing the above-mentioned "1. Sintered body of particles of a Nasicon-type solid electrolyte", and is characterized by including a step of compacting and sintering a mixed powder containing particles of a Nasicon-type solid electrolyte and particles of an aluminum-containing oxide.
[0023] The details of the Nasicon-type solid electrolyte are as described above in "1. Sintered body of Nasicon-type solid electrolyte particles". The Nasicon-type solid electrolyte particles used as a material in the manufacturing method of the present invention may be aluminum-doped or undoped. As described above, the manufacturing method of the present invention solidifies the particles by filling the grain boundary phase with a solidified melt produced by the reaction of the Nasicon-type solid electrolyte with an aluminum-containing oxide, so that the above-mentioned solidification is possible regardless of whether the Nasicon-type solid electrolyte itself is doped with aluminum. From the viewpoint of further simplifying the manufacturing method of the present invention, the preferred form of the Nasicon-type solid electrolyte particles used as a material is one that is not doped with aluminum.
[0024] The particle size and particle size distribution of the Nasicon type solid electrolyte particles are not particularly limited. In the manufacturing method of the present invention, it is not necessary to use particles with a particularly small particle size as the Nasicon type solid electrolyte particles as the material, and it is also not necessary to use particles with a strictly controlled particle size distribution, so it is possible to use inexpensive particles with high versatility, such as particles with a large particle size of the order of microns (several μm to about 10 μm) and / or particles that are not particle size controlled. Of course, particles with smaller particle sizes (for example, nanoparticles) and / or particles that are particle size controlled can also be used as materials.
[0025] The aluminum-containing oxide is not particularly limited as long as it is an oxide containing aluminum element, and oxides having a composition further containing other elements (e.g., sodium, silicon, and / or zirconium, etc.) are also acceptable. A preferred example of the aluminum-containing oxide is aluminum oxide, and more preferably Al 2 O 3 Examples include:
[0026] The particle size and particle size distribution of the aluminum-containing oxide particles are not particularly limited as long as they can be inserted between the particles of the Nasicon-type solid electrolyte. For example, the average particle size of the aluminum-containing oxide particles can be, for example, 70 nm or less, preferably 60 nm or less, more preferably 55 nm or less. The average particle size is determined by taking an electron micrograph using a TEM (high-resolution transmission electron microscope) and measuring the cross-sectional area of 100 particles, and taking the measured value as the area of the circle corresponding to the diameter as the particle size, and the arithmetic average is the average particle size. In the manufacturing method of the present invention, since general-purpose reagents can be used as materials, in reality, no special control is required, as with the particles of the Nasicon-type solid electrolyte.
[0027] The content of the aluminum-containing oxide particles contained in the mixed powder is not particularly limited as long as it does not impair the effects of the present invention. For example, the content of the aluminum-containing oxide particles per 100 mol% of the total of the solid electrolyte particles and the aluminum-containing oxide particles is 1 to 25 mol%, 1 to 20 mol%, or 1 to 15 mol%, preferably 2 to 10 mol%, more preferably 3 to 7 mol%, and further preferably 3.5 to 5.5 mol%.
[0028] The mixed powder containing the particles of Nasicon-type solid electrolyte and the particles of aluminum-containing oxide can be prepared by mixing both components. The method of mixing both components is not particularly limited, and a known method can be appropriately selected according to the manufacturing scale, etc. Specific examples of the method include manual mixing using a mortar and mechanical mixing using a ball mill, etc.
[0029] The temperature at which the mixed powder is compacted and sintered may be any temperature at which the Nasicon-type solid electrolyte and the aluminum-containing oxide react to produce a molten material, and may be appropriately determined depending on the type of Nasicon-type electrolyte used.
[0030] The conditions for compacting the mixed powder are not particularly limited, but may be, for example, 1 to 200 MPa, preferably 5 to 100 MPa, and more preferably 10 to 40 MPa.
[0031] Specific temperatures for sintering the mixed powder include, for example, 1100 to 1250°C, and from the viewpoint of further increasing the density, preferably 1120 to 1220°C, more preferably 1140 to 1210°C, even more preferably 1160 to 1210°C, and even more preferably 1180 to 1210°C. These temperatures are suitable for the sodium-containing oxide (the above general formula Na s X 1 t X 2 u O v This is particularly preferably applied when a compound represented by the formula (I), preferably NZSP, is used.
[0032] The sintering is carried out at the above temperature for, for example, 1 to 20 hours, preferably 2 to 15 hours, and more preferably 4 to 10 hours.
[0033] The sintering step may further include a pre-sintering step and a main sintering step, in which case the above-mentioned sintering temperature conditions and sintering time conditions may be applied to the main sintering step. As the temperature conditions in the pre-sintering step, within the above-mentioned sintering temperature conditions, a temperature that is preferably 50 to 150°C, and preferably 80 to 120°C, lower than the temperature conditions in the main sintering step may be adopted. As the time conditions in the pre-sintering step, a time that is about 1 / 20 to 1 / 5, and preferably about 1 / 14 to 1 / 10 of the time conditions in the main sintering step may be adopted.
[0034] In the manufacturing method of the present invention, the mixed powder is compressed and sintered, and the Nasicon solid electrolyte reacts with the aluminum-containing oxide to generate a new melt, which fills the grain boundary phase consisting of the gaps between the particles of the Nasicon solid electrolyte. In other words, in the manufacturing method of the present invention, a molten sintering aid is generated "in situ" when the particles of the Nasicon solid electrolyte come into contact with the aluminum-containing oxide particles during sintering, and then liquid phase sintering proceeds. Since the melt is generated in the very gaps between the particles of the Nasicon solid electrolyte, the followability of the melt in the gaps at the grain boundaries is good. As a result, the generated melt can easily fill the gaps regardless of the size and variation of the gaps. Therefore, regardless of the size and particle size distribution of the particles of the Nasicon solid electrolyte, and regardless of the compounding ratio (mol %) of the Nasicon solid electrolyte and the aluminum-containing oxide in the melt, it is possible to easily obtain a dense sintered body.
[0035] [3. Aqueous-non-aqueous hybrid secondary batteries] The above "1. Sintered body of particles of Nasicon-type solid electrolyte" is a sintered body with excellent ionic conductivity, compactness, and water resistance, and is therefore useful as a solid electrolyte separator for aqueous-nonaqueous hybrid secondary batteries. Therefore, the present invention also provides a solid electrolyte separator for aqueous-nonaqueous hybrid secondary batteries and an aqueous-nonaqueous hybrid secondary battery using the above "1. Sintered body of particles of Nasicon-type solid electrolyte".
[0036] The aqueous-nonaqueous hybrid secondary battery of the present invention comprises an aqueous electrolyte solution on the positive electrode side, a nonaqueous electrolyte solution on the negative electrode side, and a solid electrolyte separator using a sintered body of particles of a Nasicon type solid electrolyte interposed between the electrolyte solutions.
[0037] Classification of aqueous-non-aqueous hybrid secondary batteries includes air secondary batteries, seawater secondary batteries, etc. Therefore, specific examples of the positive electrode side aqueous electrolyte, the negative electrode side non-aqueous electrolyte, the positive electrode active material, and the negative electrode active material can be appropriately selected by a person skilled in the art according to the classification of the hybrid secondary battery. For example, a metal (such as Na, Li, etc., preferably Na) can be used as the negative electrode active material, a carbonate-based or ether-based organic electrolyte can be used as the negative electrode side non-aqueous electrolyte, air (specifically, oxygen in the air. Typically, a porous electrode such as a carbon composite material on which an oxide catalyst is supported can be used as the air electrode) can be used as the positive electrode active material, and an aqueous electrolyte (such as seawater) that dissolves the discharge product can be used as the positive electrode side aqueous electrolyte. EXAMPLES
[0038] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0039] [Test Example 1] NZSP(Na 3 Zr 2 (SiO 4 ) 2 PO 4) powder (manufactured by Toshima Seisakusho, purchased from Fujifilm Wako Pure Chemical Industries, Ltd.) was mixed with aluminum oxide (Al 2 O 3 ) powder (purchased from Sigma-Aldrich, average particle size 50 nm or less) was added to the mixture at a compounding ratio of 5 mol %, and mixed thoroughly in a mortar. The mixed powder was molded into a disk shape (φ=15 mm, t=approximately 1.2 mm) using a uniaxial press at 30 MPa, and pre-sintered by spark plasma sintering at 1100°C for 30 minutes. The pre-sintered disk was placed on platinum foil (t=0.05 mm), and then sintered at 1200°C for approximately 6 hours in an alumina crucible with a lid on, to obtain a sintered body (Example 1). In addition, Al 2 O 3 A sintered body (Comparative Example 1) was obtained in the same manner, except that no powder was used (0 mol %).
[0040] [1] Density evaluation The fracture surface of the obtained sintered body was observed by a scanning electron microscope. The secondary electron image is shown in FIG. 2 O 3 ), voids of several microns were observed at the grain boundaries of the coarse parent NZSP particles, indicating insufficient densification. 2 O 3 ), almost no voids were observed at the grain boundaries of the parent NZSP particles, and excellent density was achieved.
[0041] FIG. 2 shows a comparison of the fracture surface of the sintered body of Example 1 using scanning electron microscope images (secondary electron image and backscattered electron image). The secondary electron image and backscattered electron image in FIG. 2 were acquired at the same time at the same location. The secondary electron image shows that the sintered body has no voids and is sufficiently densified. On the other hand, the backscattered electron image shows contrasts of different brightness. In general, the brightness of a backscattered electron image depends on the atomic number. Therefore, it is suggested that the brighter regions are the NZSP component, which is the parent phase, and the components with lower brightness are the aluminum-containing components. The backscattered electron image shows that the grain boundary phase between the NZSP particles of the parent phase is filled with the aluminum-containing component, resulting in the sintered body being densified.
[0042] FIG. 3 shows an energy dispersive X-ray (EDS) spectrum obtained from the corresponding point in the backscattered electron image in FIG. 2. No aluminum-derived components were observed in the spectrum obtained from the bright area (Sp.2). This suggests that they are the parent phase, the NZSP particles themselves. On the other hand, a peak derived from aluminum was clearly observed in the spectrum obtained from the low brightness area (Sp.1). From this, it was recognized that the grain boundary phase between the NZSP parent phase particles in the sintered body of Example 1 was filled with aluminum-containing components, resulting in densification.
[0043] FIG. 4 shows the results of Example 1 (5 mol% Al 2 O 3 ) sintered body, Comparative Example 1 (0 mol% Al 2 O 3 The XRD profiles of the sintered body of NZSP and the untreated material NZSP powder are shown in Fig. 1. For comparison, the commonly known monoclinic Na 3 Zr 2 (SiO 4 ) 2 PO 4 The simulation profile of the (space group C2 / c) and its crystal structure are also shown. These are based on data number 202154 of the inorganic crystal structure database ICSD. 2 O 3 ) and Comparative Example 1 (0 mol% Al 2 O 3 The diffraction profile of Example 1 (5 mol% Al) is almost the same as that of the untreated NZSP powder. These features also matched exactly with the simulated profile. 2 O 3 It was found that the sintering conditions (1200°C, 6 hours) used to prepare Comparative Example 1 (0 mol% Al) did not cause significant structural damage to the matrix. 2 O 3 ) compared with Example 1 (5 mol% Al 2 O 3 In the case of Example 1 (5 mol% Al), an amorphous halo was observed near 2θ = 23 deg, as indicated by the downward arrow. 2 O3 It is suggested that amorphous components are present in the sample of Example 1 (5 mol% Al 2 O 3 ) is shown with a triangular symbol, ZrO 2 The peaks due to the Al component are clearly visible. This is because the NZSP particles and Al 2 O 3 The particles react with each other, and the components such as Na, P, and Si in the NZSP matrix are converted to Al. 2 O 3 When the glass is dissolved in the SiO2, a glass component with a low melting point is generated, and the residue is ZrO 2 It is believed that what remains is
[0044] [2] Water permeability evaluation FIG. 5 shows the results of Example 1 (5 mol% Al 2 O 3 ) sintered body, Comparative Example 1 (0 mol% Al 2 O 3 5 shows the results of an electrochemical comparative study of the water permeability of the sintered bodies of Comparative Example 1 and Example 1. FIG. 5(a) shows a schematic diagram of the experiment. NZSP ceramic plates (hereinafter also referred to as samples, sample plates, and partition samples) made from the sintered bodies of Comparative Example 1 and Example 1 were attached to an electrochemical cell as shown in the figure, and evaluation was performed using a three-electrode cell with a SUS plate as the working electrode, a Pt ribbon as the counter electrode, and a silver / silver chloride electrode as the reference electrode. The electrolyte was a 0.5 M aqueous sodium sulfate solution (hereinafter referred to as 0.5 M Na 2 SO 4 aq) was used. Both sides of the sample plate were polished before the experiment, and the size of the sample plate was set to a diameter φ = 15 mm and a thickness t = 1.0 mm. If the sample is not dense enough, water will permeate the sample and an electrochemical reaction will occur on the working electrode. Therefore, when the working electrode potential is swept in a less noble direction, a current resulting from the reductive decomposition of water will be observed. Figure 5(b) shows the cyclic voltammetry obtained for each sample plate.
[0045] As shown in FIG. 5(b), Comparative Example 1 (0 mol% Al 2 O 3In the sample of Example 1 (5 mol% Al), a large reduction current was observed from about 1.5 V relative to the counter electrode Na. This means that the water that permeated the inside of the partition wall sample reached the surface of the working electrode, where a reduction decomposition reaction occurred. 2 O 3 For the sample of Comparative Example 1 (0 mol% Al), almost no reduction current was observed for water decomposition. Even under extremely strong reduction conditions of 0.2 V vs. Na, the value was about -30 μA. 2 O 3 Considering that the value under the strongly reducing conditions in the sample of Example 1 (5 mol% Al 2 O 3 ) sample achieved an improvement in water impermeability of about 1,000 times.
[0046] [3] Making a half cell Example 1 (5 mol% Al 2 O 3 A hybrid aqueous-nonaqueous battery was fabricated using an NZSP sintered plate made from a sintered body of 1M NaTFSA in EC / DEC=1.0 as a separator. 3 LiTi 5 O 12 (hereinafter abbreviated as NTO) was used as the negative electrode. A glass filter with a thickness of t = 0.2 mm was sandwiched between the NZSP sintered plate and the negative electrode active material to hold the negative electrode electrolyte. The electrolyte for the positive electrode was 0.5M Na 2 SO 4aq was used. Figure 6(b) shows the results of cyclic voltammetry measurements of a half cell with a silver / silver chloride electrode as the reference electrode and a Pt ribbon as the counter electrode. When the potential was scanned in the less noble direction, a rise in the reduction current was observed at approximately 0.8 V relative to the Na counter electrode. This is due to the Na absorption reaction of the NTO anode. When the potential was scanned in the more noble direction, a clear oxidation peak due to Na release was confirmed in the same potential range. The current values of the redox peaks were each 400 μA or more, which is significantly larger than the leakage current of 30 μA confirmed in Figure 5(b). This suggests that the ions contributing to these redox currents are not due to the penetration of water, but are brought about by the ionic conduction of the NZSP sintered plate itself.
[0047] [4] Making a full battery Hydrogen peroxide was added to the electrolyte of the positive electrode at 3 wt% H 2 O 2 -0.5M Na 2 SO 4 The electrolyte was aq. Furthermore, a highly active carbon cloth electrode (LT-140EW, manufactured by BASF) was used for the positive electrode to fabricate a simple full battery. Here, hydrogen peroxide functions as a sacrificial active material to reduce the overvoltage of the redox reaction at the positive electrode. In other words, this battery is not a complete secondary battery, but it has a sufficient structure to evaluate the basic performance of the separator. The results are shown in Figure 7.
[0048] In Figure 7, the irreversible reaction seen in the first cycle is due to the negative electrode NTO. After the second cycle, the charge and discharge were relatively stable, reaching 70 mAhg on the negative electrode basis. -1 On the other hand, during constant current charging and discharging, the average voltage was about 2.4 V, which is a relatively high voltage for a sodium-based secondary battery using an aqueous electrolyte.
[0049] [5] Summary of Test Example 1 Al is added as a sintering aid to the parent NZSP particles. 2 O 3By adding Al and sintering, a dense sintered body was obtained. Moreover, it was confirmed that the density could be sufficiently improved even if commercially available coarse NZSP particles were used as the parent phase. During the sintering process, the NZSP particles of the parent phase and Al 2 O 3 The aluminum-containing components react with the particles, producing a molten material consisting of aluminum-containing components. It is believed that this molten material fills the gaps at the grain boundaries between the NZSP particles, achieving densification of the sintered body. Because the aluminum-containing components are highly water-resistant, the resulting NZSP sintered body functions as a partition wall for aqueous batteries. This was confirmed by the performance of an aqueous-nonaqueous hybrid sodium-ion battery that uses NTO for the negative electrode. Cyclic voltammetry measurements of the prototype battery confirmed a reversible redox peak, confirming its operation as a secondary battery.
[0050] [Test Example 2] Al 2 O 3 A sintered body (Example 2) was produced in the same manner as in Example 1 of Test Example 1, except that the amount of was changed to 10 mol %.
[0051] Sintering temperature was set to 1250℃, and Al 2 O 3 Sintered bodies (Comparative Example 2 and Example 3, respectively) were produced in the same manner as in Comparative Example 1 and Example 1 of Test Example 1, except that the amount of was changed to 10 mol %.
[0052] The appearance of the produced sintered body is shown in Figure 8. When the firing temperature was 1200°C (a), no difference in appearance was observed between Comparative Example 1 and Example 2. On the other hand, when the firing temperature was 1250°C (b), the change in appearance in Comparative Example 2 was almost the same as in (a), but in Example 3, the edges of the pellets were found to have a rounded appearance, confirming traces of the sample melting during the firing process.
[0053] Furthermore, for Comparative Example 2 and Examples 2 and 3, the water permeability was evaluated in the same manner as in [2] of Test Example 1. The results are shown in Figure 9. In Figure 9, the results of Comparative Example 1 are also shown.
[0054] The vertical axis of FIG. 9(a) is in mA scale, and the vertical axis of FIG. 9(b) is in μA scale. Compared with Comparative Examples 1 and 2, Examples 2 and 3 had improved water impermeability. 2 O 3 When comparing the same amount of Al added, in the case of no addition (0 mol%), the water impermeability tended to be higher in the case of firing at 1250°C (Comparative Example 2) than in the case of firing at 1200°C (Comparative Example 1). This is thought to be because the sintering of NZSP itself progresses by firing at 1250°C. However, the water impermeability of both cases was insufficient. On the other hand, in the case of adding 10 mol%, the water impermeability tended to be higher in the case of firing at 1200°C (Example 2) than in the case of firing at 1250°C (Example 3). 2 O 3 When adding Al, the temperature condition of 1200℃ is better than that of NZSP and Al. 2 O 3 It is considered that the degree of reaction with Al and / or melting of the grain boundary phase product mainly composed of Al is more appropriate, and this more favorably contributes to improving the density of the sintered body.
[0055] [Test Example 3] Al 2 O 3 Sintered bodies (Examples 4 and 5) were produced in the same manner as in Example 1 of Test Example 1, except that the amount of was changed to 2 mol % or 4 mol %. For Examples 4 and 5, water permeability was evaluated in the same manner as in [2] of Test Example 1. The results are shown in Figure 10. Figure 10 also shows the results of Example 2 and Comparative Example 1.
[0056] The vertical axis in Fig. 10(a) is in mA scale, and the vertical axis in Fig. 10(b) is in μA scale. 2 O 3 Compared to Comparative Example 1, which does not contain any additives, 2 O 3 Even with an addition amount of only 2 mol% (Example 5), the water impermeability was dramatically improved. 2 O 3 The amount of addition of 4 mol% (Example 4) was sufficient. Furthermore, taking into account the improvement in yield, 2 O 3The optimum amount of addition was 5 mol%. When particles with a homogenized particle diameter were used as NZSP particles instead of the commercially available coarse particles used in this test example, the size of the gaps between the particles (grain boundary phase) became smaller, so the optimum Al content was 1.0 mol%. 2 O 3 It is believed that the amount added will be less.
[0057] [Test Example 4] 1M LiPF 6 In the negative electrode electrolyte, an ionic polymer gelling agent (Kanto Chemical) was added to the electrolyte solution prepared by dissolving in propylene carbonate solvent, and the solution was soaked in a glass filter with a thickness of t = 0.2 mm, and then integrated with the negative electrode NTO to form a gel. The gelling process increases the electrolyte retention rate, which is expected to improve the cycle characteristics of the battery.
[0058] The gelled negative electrode electrolyte and 0.5M Na 2 SO 4 The cycle characteristics of the half-cell were shown using an aqueous solution and the sintered body of Example 1 as a separator. The results are shown in Figure 11. As shown in Figure 11, the behavior was stable from 30 cycles to about 80 cycles, and the operation was good for an aqueous-nonaqueous hybrid battery. Further improvement in cycle characteristics is expected by improving the electrolyte used in the negative electrode.
[0059] [Test Example 5] Al 2 O 3 A sintered body (Example 6) was produced in the same manner as in Example 1 of Test Example 1, except that the amount of was changed to 20 mol %. Thermal analysis was performed on the sintered bodies of Example 6 and Comparative Example 1. The results are shown in Fig. 12. In Fig. 12, the vertical axis shows the temperature differential value d(DTA) / dT of the result of differential thermal analysis (DTA).
[0060] As shown in FIG. 12, the peaks observed in the temperature range of 1200°C or higher coincide with the peritectic point of the raw material powder NZSP (the temperature at which the surface layer of the crystal melts and partial phase separation occurs). On the other hand, a peak observed at a lower temperature of around 1100°C is prominent in Example 6, and this is Al 2 O 3 It is considered that this is the reaction temperature between NZSP and ZnO.
[0061] [Test Example 6] The sintering temperature was set to Al in Test Example 5. 2 O 3 The reaction temperature between Al and NZSP was confirmed to be 1100℃. 2 O 3 Sintered bodies (Examples 7 and 8, and Comparative Example 3, respectively) were produced in the same manner as in Example 1 of Test Example 1, except that the amount of added was changed to 10 mol%, 4 mol%, or 0 mol%. For Examples 7 and 8, and Comparative Example 3, water permeability was evaluated in the same manner as in [2] of Test Example 1. The results are shown in FIG. 13. In FIG. 13, the results of Examples 2, 4, and 5 and Comparative Example 1 are also shown.
[0062] The vertical axis in Fig. 13(a) is in mA scale, and the vertical axis in Fig. 13(b) is in μA scale. 2 O 3 In the case of no additive, significant water permeation was confirmed at both the sintering temperatures of 1100°C (Comparative Example 3) and 1200°C (Comparative Example 1). 2 O 3 In the case of addition, water impermeability was dramatically improved not only when the sintering temperature was 1200° C. (Example 5) but also when the sintering temperature was 1100° C. (Example 7).
[0063] As can be seen from FIG. 13(b), it was confirmed that in order to further improve water impermeability, a sintering temperature of 1200°C (Examples 2 and 4) is more desirable than a sintering temperature of 1100°C (Examples 7 and 8).
[0064] [Test Example 7] The sintered body of Comparative Example 1 (Al 2 O 3FIG. 14 shows a secondary electron image of a scanning electron microscope (SEM) of a powder (without additives, sintered at 1200°C). From the irregularities and voids seen in the image of FIG. 14, it is recognized that the commercially available NZSP powder used as the material in Test Examples 1 to 5 is composed of secondary particles of about 3 to 10 μm that are formed by further aggregation of primary particles of about 0.5 to 1 μm. The bonding state between the secondary particles is not good, and voids of the order of several μm are included. With a powder having such particle characteristics, it is not possible to produce a dense sintered body inherently, and even if the sintering temperature is increased to 1250°C, the desired density cannot be obtained, as shown in FIG. 9 (Comparative Example 2). According to the present invention, such an NZSP powder, which is inherently difficult to densify, is used as the material, and a commercially available Al 2 O 3 By simply adding, mixing and sintering, it is possible to dramatically improve the density of the resulting sintered body. The excellent performance of the sintered body thus obtained is confirmed by its function as a solid electrolyte separator for aqueous secondary batteries.
Claims
1. A sintered body of particles of a Nasicon type solid electrolyte, The particles, and A sintered body comprising a grain boundary phase made of a melt-solidified product of the solid electrolyte and an aluminum-containing oxide, which bonds the particles together.
2. 2. The sintered body according to claim 1, wherein the Nasicon type solid electrolyte is a sodium-containing oxide.
3. The sodium-containing oxide is Na 3 Zr 2 (SiO 4 ) 2 P.O. 4 The sintered body according to claim 2 ,
4. A method for producing a sintered body of particles of a Nasicon type solid electrolyte, comprising the steps of: The method includes a step of compacting and sintering a mixed powder containing particles of the solid electrolyte and particles of an aluminum-containing oxide.
5. The method according to claim 4, wherein the powder sintering temperature is 1100 to 1250°C.
6. 5. The method according to claim 4, wherein in the mixed powder, the content of the aluminum-containing oxide particles is 1 to 25 mol % per 100 mol % in total of the solid electrolyte particles and the aluminum-containing oxide particles.
7. A solid electrolyte separator for an aqueous-non-aqueous hybrid secondary battery, comprising the sintered body according to claim 1.
8. 8. An aqueous-nonaqueous hybrid secondary battery comprising: a positive electrode-side aqueous electrolyte; a negative electrode-side nonaqueous electrolyte; and the solid electrolyte separator according to claim 7 interposed between the electrolytes.